Parental preferences on diagnostic imaging tests for paediatric appendicitis. Issue 4 (17th December 2018) - Martinez-Rios, Claudia; McKinney, Jennifer R; Al-Aswad, Nadine; K. Shergill, Arvind; Louffat, Ada F; Sung, Lillian; Thomas, Karen E; Schuh, Suzanne; Tomlinson, George; Moineddin, Rahim; Doria, Andrea S
Abstract: Objectives: To determine parental preferences for diagnostic imaging tests (DITs) for paediatric appendicitis, to rank the attributes impacting the DIT selection and to identify DIT attributes that would cause parents to switch their DIT. Methods: Parents of children who had an abdominal ultrasound (US) for right lower quadrant pain were interviewed. Two DITs were compared at a time, parents were asked to indicate their preferred test and to rank its attributes according to the impact each attribute had on their selection. The strength of their preference for the chosen DIT was measured by systematically adjusting attributes of the chosen DIT until the parent changed their choice. Results: Fifty parents were interviewed. For US versus CT, more parents preferred US (68%, P=0.02) with higher importance ranks for cancer risk (P<0.0001), test accuracy (P=0.04), pain during test (P=0.3), and scan length (P<0.0001); and lower ranks for sedation (P=0.02), intravenous (IV) (P<0.02), and oral contrast (P=0.06). For US versus MRI, parents preferred MRI (78%, P<0.0001) with higher importance ranks for accuracy (P=0.2), pain during test (P=0.06), and scan length (P=0.06); and lower for noise (P<0.0001), claustrophobia (P<0.0001), use of IV contrast (P=0.06), and sedation (P=0.2). Conclusion: US and MRI were the DIT preferred by parents for the investigation of acute paediatric appendicitis.